Efek Pemutihan Pajak Kendaraan Bermotor dan Penerapan Pembayaran Pajak Online Kendaraan Bermotor pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Zana Zhafirah Kusuma Adjie; Aisyahturrahmi Aisyahturrahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Tax relief and the ease of the tax payment process are factors expected to enhance taxpayer compliance. This study aims to examine the effect of Vehicle Tax Bleaching and the implementation of online vehicle tax payments on the compliance of motor vehicle taxpayers. This study uses a quantitative approach and the data used in this research is primary data by distributing questionnaires to 100 motor vehicle taxpayers in the city of Surabaya. This study uses the purposive sampling method with SmartPLS 3.0 to conduct data analysis. The results of this study explain that Vehicle Tax Bleaching does not have an impact on motor vehicle taxpayer compliance, whereas the implementation of online motor vehicle tax payments does have an impact on taxpayer compliance.